The Black Sea is in danger: echoes of war - Artemenko, Pavlo (Запоріжжя: НБ ТДАТУ, 2025)
The Black Sea is a unique body of water that stands out from other seas and oceans. Many rivers flow into the Black Sea, carrying significant volumes of fresh water, so the salinity of the Black Sea is almost twice as low as that of ocean waters.However, its semi-enclosed nature and the presence of a large volume of oxygen-free water make the Black Sea vulnerable to human activity and climate change [Садогурська, 2023].
Keywords: Black Sea; Kakhovka hydroelectric; war